Процес задоволення потреб споживачів у послугах освіти ВНЗ - Букало, Надія Артемівна; Bukalo, Nadiia A.; Войтович, Сергій Ярославович; Voitovych, Serhii Ya. (Луцький національний технічний університет, 2009)
У статті розглянуто процес задоволення потреб споживачів в одержанні освітніх послуг вищих навчальних закладів, зокрема: виникнення освідомлення таких потреб; внутрішні й зовнішні фактори впливу на процес задоволення потреб в одержанні вищої освіти; мотиви за якими людина діє тим або іншим способом у сфері споживання; вимоги до процесу задоволення потреб споживачів в одержанні освітніх послуг. In the article the process of satisfaction of necessities of users is considered in the receipt of educational services of higher educational establishments, in particular: origin of awareness of such necessities; internal and external factors of influence on the process of satisfaction of requirements are in the receipt of higher education; reasons after which a man operates those or by other method in the field of consumption; requirement to the process of satisfaction of necessities of users in the receipt of educational services.
The process of customer satisfaction in the services of education institution of higher learning
Keywords: освітні послуги; вищі навчальні заклади (ВНЗ); процес надання освітніх послуг; потреби споживачів; educational services; higher educational establishments; process of grant of educational services; necessity of users